Exchange of Information in Tax Matters - Szwajdler, Paweł (Journal of Education, Health and Sport, 2017)
The main aim of this paper is to present issues related to exchange of tax information. The author focuses on models of exchange of information and boundaries of obligations in reference to above-mentioned problems. Automatic exchange of information, spontaneous exchange of information and exchange of information on request are analysed in this work on the base of OECD Convention on Mutual Administrative Assistance in Tax Matters, Council Directive 2011/16 and OECD Model Agreement on Exchange of Information in Tax Matters. In the summary, it was showed that the most efficient method of exchange of tax information is automatic exchange of information. Furthermore, it was stated that exchange on request can be related to negative phenomenon such as fishing expedition. Spontaneous exchange of information is thought to play only supportive role. The author also considers that boundaries of exchange of information in tax matters were regulated so as to protect jeopardised raison d’ <span style="font-family: 'Times New Roman', serif; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">État<span style="font-family: 'Times New Roman', serif; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">.